Children's rights in Algeria: History, achievements and research evidence. Issue 2 (June 2015) - Boussena, Mahmoud; Tiliouine, Habib
This article sought to analyse the implementation and promotion of children's rights in Algeria from a historical and contextual perspective. This analysis was backed with legislative texts and research evidence. The results indicate that during the colonial era (1830–1962), no tangible policies were sought to protect the people and their children from poverty and ignorance. But the post-colonial era witnessed a beginning of interest in the status of the children and their needs within a socialist orientation. However, the democratic shift of 1989 was accompanied with social turmoil for about 10 years. During these tragic events, the country started to adapt its national child legislation to the requirements of the international legislation since some successes have been achieved in the areas of registering new births and providing education and health-care opportunities for children. But a great deal of work is yet to be done in the areas of ensuring quality education; quality health care; efficient protection from abuse and violence in families, schools and public spaces; enhancing participation in family and school decision-making; and provisions for leisure and culture opportunities. Recommendations include the call for the Algerian government to appoint an official body to provide indicators to evaluate and monitor the protection, respect and promotion of the rights of the child nationwide and collect and combine research data. Leisure and culture opportunities and child's participation should also be prioritised. Furthermore, the Ministry of Education should reinforce the teaching of child's rights in official curricula, use modern information technologies and should issue compulsory measures to publicise Convention on the Rights of the Child in school spaces. The role of scientific research, mass media, non-governmental organisations and youth organisations should also be further supported.